Optimization of Process Parameters by Response Surface Methodology for Methylene Blue Removal Using Cellulose Dusts - Seyed Hassan Sharifi Pajaie; Saltanat Archin; Ghasem Asadpour (Civil Engineering Journal, 2018)
This study was aimed to use Cellulose dusts (CD) produced in drying section of paper mills of paper making industry as a potential adsorbent to remove methylene blue (MB) dye from aqueous solution.  The adsorbent was characterized by scanning electron microscopy and Fourier transform infrared spectrometer and X-ray Diffraction. The influences of the effective parameters including pH solution, adsorbent dosage, initial MB concentration, and contact time were optimized by CCD which stands for central composite design. The influence of these parameters on the adsorption capacity was analyzed using the batch process. The accuracy of the equation that is produced by CCD was affirmed by the variance analysis and also by calculating the correlation coefficient that connects the predicted and the empirical values of the percentage of removed MB dye. Maximum removal percentage of MB dye (98.05 %) which obtained at pH 9.84, adsorbent dosage 4.38 g L-1, MB concentration 75.50 g L-1 and time 208.13 min. Freundlich, Temkin, Harkins-Jura and Langmuir isotherms are used to analyze the empirical data. Results revealed that the data is in a satisfying agreement with the Freundlich isotherm (R2= 0.99). Pseudo-first order, Pseudo-second-order, Elovich and Intraparticle diffusion models were used to fit the kinetic data and it is found out that MB dye’s adsorption onto CD has a good agreement with the pseudo-second-order kinetic model. The results showed that CD can be an efficient and low-cost adsorbent for methylene blue adsorption.